Heidelberg ETV score to assess success of ETV in patients with occlusive hydrocephalus: a retrospective single-center study - Issa, Mohammed; Younsi, Alexander; Paggetti, Filippo; Miotk, Nikolai; Seitz, Angelika; Bendszus, Martin; Wisoff, Jeffrey H.; Unterberg, Andreas; El Damaty, Ahmed (Neurosurgical review, 2023)
In aqueduct stenosis, pressure difference below and above level of obstruction leads to bulging of third ventricular floor (TVF) and lamina terminalis (LT). Endoscopic third ventriculocisternostomy (ETV) is the standard treatment in these patients. We tried to assess success of ETV depending on those two radiological changes in aqueduct stenosis. We implemented “Heidelberg ETV score” retrospectively to assess the state of TVF as well as LT in same manner in midsagittal MR image. Every patient had a preoperative, direct, 3-months and one-year postoperative score from -2 to + 2. We correlated the scores to clinical course to decide whether the score is reliable in defining success of ETV. Between 2017-2021, 67 (mean age 25.6 ± 23.9y) patients treated with ETV were included. Success rate of primary and Re-ETVs was 91% over 46.8 ± 19.0 months. A marked shift of score to the left after surgery in success group was noticed through the distribution of score immediate postoperative, 3-months later; 70.2% showed (+ 2) before surgery, 38.9% scored (0) after surgery and 50.9% showed further score drop to (-1) 3 months later, p < 0.001. In cases of failure, there was initial decrease after surgery followed by increase with ETV-failure (mean time to failure: 7.2 ± 5.7 months) in 100%. Significant difference was noticed in Heidelberg score at postoperative 1-year- and failure-MRI follow-up between two groups, p < 0.001. Heidelberg score describes anatomical changes in third ventricle after ETV and can serve in assessment of MR images to define success of the procedure in patients with aqueduct stenosis.